Evaluation of cooling and freezing systems of bovine semen - Dias, Erika Aline Ribeiro; Campanholi, Suzane Peres [UNESP]; Rossi, Guilherme Fazan [UNESP]; Freitas Dell'Aqua, Camila de Paula [UNESP]; Dell'Aqua, José Antonio [UNESP]; Papa, Frederico Ozanam [UNESP]; Zorzetto, Mariana Furtado [UNESP]; de Paz, Claudia Cristina Paro; Oliveira, Letícia Zoccolaro; Mercadante, Maria Eugênia Zerlotti; Monteiro, Fabio Morato (Elsevier, 2018)
Semen cryopreservation comprises different steps, among them are the cooling and freezing rates which significantly influence the quality of thawed sperm. Different systems with variable freezing rates are used for freezing bull semen in the field, with a consequence of variable success rates. The objective of this study was to compare different systems for freezing bull semen in the field. Five cooling methods of semen and two methods for the subsequent freezing phase (5 × 2 factorial scheme) were used. Two to four ejaculates were collected from 12 bulls with an electroejaculator. The ejaculates were diluted in BotuBov® to a concentration of 50 × 106 spermatozoa/mL in 0.5-mL straws. After dilution, the straws were cooled to 5 °C in five cooling systems: TK 4000® at a cooling rate of −0.25 °C/min (R1); TK 4000® at a rate of −0.5 °C/min (R2); Minitube® refrigerator at a rate of −2.8 °C/min (R3); Botutainer® at a rate of −0.65 °C (R4), and domestic refrigerator at a rate of −2.0 °C/min (R5). After stabilization at 5 °C for 4 h, these straws were then submitted to two freezing systems: TK 4000® at a freezing rate of −15 °C/min (C1) and Styrofoam box with liquid nitrogen at a rate of −19 °C/min (C2). Sperm kinetics were evaluated by computer-assisted sperm analysis at four time points: in fresh semen, after cooling, post-thawing, and after the rapid thermal resistance test (TRT). In addition, plasma and acrosomal membrane integrity, mitochondrial potential and intracellular H2O2 were analyzed after thawing by flow cytometry. The R1, R2 and R4 cooling systems were the most efficient in preserving sperm viability, membrane integrity and intracellular H2O2. Samples frozen in the C1 system exhibited better post-thaw and post-TRT kinetics than C2 samples. In conclusion, slower cooling curves in conjunction with a constant freezing rate obtained with the programmable unit were more efficient for freezing bull semen in the field.
Keywords: CASA; Cooling rate; Cryopreservation; Nellore; Sperm viability